Detoxification of Distillery Wastewater by AOP Fenton for the Enhancement of Biogas Production (Universitas Negeri Semarang, 2022)
Distillery wastewater from the bioethanol industry contains a high level of organic content which can be converted into biogas. However, the presence of toxic compounds in this wastewater could inhibit biogas production. Therefore, prior detoxification of distillery wastewater is required. Fenton, one of the Advanced Oxidation Process (AOP) methods, was selected due to its high performance to degrade organic pollutants, short reaction time, and the process is simple and easy. Additionally, this method can also be used as a pretreatment for biogas production. This paper aims to study the improvement of biogas production from distillery wastewater by applying AOP Fenton as a pretreatment method. The experiment consists of two stages, the first was application of AOP Fenton to the distillery wastewater in order to determine its effect on the concentration of COD and some toxic compounds such as phenol and sulfate. The second stage was biogas production through anaerobic digestion process, which was carried out under two conditions of raw materials: (i) distillery wastewater without pretreatment of AOP Fenton as a control and (ii) distillery wastewater that has been treated with AOP Fenton as pretreatment. Results show a remarkable decrease in COD concentration by 45%, phenol (63%), and sulfate (18,6%) from distillery wastewater after applying AOP Fenton. It implies that the application of AOP Fenton significantly detoxified distillery wastewater. As a biogas pretreatment, this method also increased biogas production by 33% higher, from 2.399 mL (without pretreatment) to 3.191 mL (with pretreatment). It indicates that AOP Fenton increased the biodegradability of distillery wastewater. Thus, it was easier to be converted into biogas.